Gut Dysbiosis in Selected Gynecological Diseases Associated with Female Infertility: A Scoping Review - Łukasz Nowakowski; Katarzyna Warchoł; Agnieszka Kuźniar; Barbara Zimoń; Michał M. Skoczylas; Paweł Marzec; Grzegorz Krawczyk; Dorota Jegorow; Robert Pankiewicz; Andrew Z. Warchoł; Maciej Banach; Kinga Kuranty; et al. (Journal of Clinical Medicine, 2026)
Background/Objectives: Female infertility represents a significant public health issue. Available evidence supports the hypothesis that the gut microbiota may play an essential role in women’s reproductive health and may serve as a diagnostic or prognostic biomarker in specific gynecological disorders. A substantial part of current research concerns disturbed communication between the hypothalamic–pituitary–ovarian axis and the gut microbiota, providing the basis for analyzing this phenomenon as the gut–ovary axis or the gut–vagina–ovary axis. The primary aim of this scoping review was to map the available evidence on the relationship between gut microbiota composition and female infertility, with particular emphasis on polycystic ovary syndrome (PCOS, currently polyendocrine metabolic ovarian syndrome, PMOS) endometriosis, and uterine fibroids. Methods: The review was conducted in accordance with the PRISMA Extension for Scoping Reviews (PRISMA-ScR). PubMed, Scopus, and Google Scholar were searched using terms related to gut microbiota, female infertility, PCOS, endometriosis, and uterine leiomyomas. Peer-reviewed publications in English published between 2015 and 2025 were considered. The included studies were descriptively synthesized to identify recurring microbiota patterns and research gaps. Results: The reviewed evidence indicates that gut dysbiosis may be associated with selected gynecological disorders affecting fertility, including PCOS, endometriosis, and uterine fibroids. The gut microbiome may have potential value as a biomarker supporting diagnosis, treatment selection, and prognosis. Conclusions: The gut microbiome represents a promising but still insufficiently validated area in the management of gynecological diseases associated with female infertility. Further high-quality clinical studies are needed to verify the effectiveness of microbiome-based therapies and to develop evidence-based guidelines for managing infertility associated with gut dysbiosis.